2021
DOI: 10.3390/healthcare9020220
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Lockdown, Population Density, and Financial Distress Brings Inadequacy to Manage COVID-19: Leading the Services Sector into the Trajectory of Global Depression

Abstract: The service industry provides distributive services, producer services, personal services, and social services. These services largely breakdowns due to restrictions on border movements, confined travel and transportation services, a decline in international tourists’ visitation, nationwide lockdowns, and maintaining social distancing in the population. Although these measures are highly needed to contain coronavirus, it decreases economic and financial activities in a country, which requires smart solutions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…Later, many countries followed the Chinese example, aligning their strategies with the level of risk of COVID-19 and adapting the economic situation to prevent and fight new epidemics [5,6]. When unprecedented emergencies occur, not solely healthcare but also policy steps intended for securing public and economic vitality should Sustainability 2022, 14, 7192 2 of 32 be implemented, such as keeping social distance, promoting the 'Stay at home' campaign, and personal protection practices, including following personal hygiene and wearing facial masks [7,8]. Successful implementation of these measures must be bolstered by the general public's active involvement, regardless of pandemics being primarily a health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Later, many countries followed the Chinese example, aligning their strategies with the level of risk of COVID-19 and adapting the economic situation to prevent and fight new epidemics [5,6]. When unprecedented emergencies occur, not solely healthcare but also policy steps intended for securing public and economic vitality should Sustainability 2022, 14, 7192 2 of 32 be implemented, such as keeping social distance, promoting the 'Stay at home' campaign, and personal protection practices, including following personal hygiene and wearing facial masks [7,8]. Successful implementation of these measures must be bolstered by the general public's active involvement, regardless of pandemics being primarily a health issue.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the government's encouragement through a touch of policy with a tendency to community economic growth is one of the strong aspects of overcoming the impact of the pandemic on the economic sector. On the other hand, Yu et al (2021) also revealed that pandemic control policies such as restrictions on social activities could reduce the outbreak effectively. However, these policies certainly conflicted with matters in the economic sector.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the exhaustion of healthcare capacities, all patients with other serious acute or chronic diseases may suffer the consequences [ 5 ]. Furthermore, pandemics have huge societal implications, the whole economy can be compromised [ 6 , 7 ].…”
Section: Pandemic Periods – a Special Case Of Uncertaintymentioning
confidence: 99%